ISOKINETIC EXERCISE TRAINING ON IMPROVEMENT IN MUSCULAR STRENGTH IN KNEE OSTEOARTHRITIS- A META-ANALYTIC REVIEW - NARESH BHASKAR RAJ,; Dr. SOUMENDRA SAHA,; PROF. Dr. AMRAN BIN SHOKRI,; Dr. SRILEKHA SAHA,; PROF. Dr. ABDUL NAWFAR SADAGATULLAH,; PROF. Dr. HAIRUL ANWAR HASHIM,; PROF. Dr. MOHAMED SAAT ISMAIL,; CHOO MORLEY LIZA, (International Journal of Pharma and Bio Sciences, 2016)
Osteoarthritis is a disease with destruction of cartilage and damage of the subchondral bone. The prevalence of osteoarthritis has been on the rise due to increase in the elderly population. Isokinetic training has been used to improve the strength of muscles and to measure the peak torque of muscle in normal individuals and in patients with orthopaedic crises. Isokinetic exercises are frequently used in the management of osteoarthritis of knee; however the true effect remains unknown. Therefore the objective of the review was to determine the magnitude of the effect of isokinetic training on strength in patients with osteoarthritis of knee. An extensive literature search was done on Web of Science, ProQuest, PubMed, Ebscohost, and CINAHL between 1990 and 2014. Ten articles measuring the effect of isokinetic training on osteoarthritis of knee were included and methodologically assessed. Data from the trials were extracted based on the demographic characteristics, outcomes measured, isokinetic training protocol and the other interventions used. Standardized effect sizes with 95%confidence interval (CIs) were calculated from the pre-intervention and post intervention means of the isokinetic training group and other intervention group. About five articles were analysed for improvement in strength. Pooled analysis of the results from the articles included favoured isokinetic training as a modality for improving strength. Isokinetic training was found to be beneficial in improving the strength of muscle in patients with osteoarthritis. Yet there is no definitive evidence to confirm the beneficial effects of isokinetic training on osteoarthritis of knee.